(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
With the outbreak of the pandemic in the Philippines, education was one of the most affected by it. The education department has implemented numerous adjustments to ensure that every Filipino can have an education continuously despite the pandemic. Teachers are among those who have been most affected by these changes in education. Hence, this study aims to assist and provide competent approaches to all ideal teachers for reducing the difficulties of teaching in a virtual classroom. Quantitative research was used as the research design for the study while utilizing a random sampling to gather respondents in assessing the level of challenges encountered by the faculty of Bestlink College of the Philippines on virtual teaching. This sampling technique seeks an unbiased selection of respondents because every individual has the same probability of being chosen as a respondent. Using the instrument of the study, the questionnaire, the researchers surveyed to determine the challenges encountered by the faculty in virtual teaching. With the outbreak of the pandemic in the Philippines, education was one of the most affected by it. The education department has implemented numerous adjustments to ensure that every Filipino can have an education continuously despite the pandemic. Teachers are among those who have been most affected by these changes in education. Hence, this study aims to assist and provide competent approaches to all ideal teachers for reducing the difficulties of teaching in a virtual classroom. Quantitative research was used as the research design for the study while utilizing a random sampling to gather respondents in assessing the level of challenges encountered by the faculty of Bestlink College of the Philippines on virtual teaching. This sampling technique seeks an unbiased selection of respondents because every individual has the same probability of being chosen as a respondent. Using the instrument of the study, the questionnaire, the researchers surveyed to determine the challenges encountered by the faculty in virtual teaching.